Securing Converged IP Networks - Macaulay, Tyson (CRC Press, 2009)
Internet Protocol (IP) networks increasingly mix traditional data assets with traffic related to voice, entertainment, industrial process controls, metering, and more. Due to this convergence of content, IP networks emerge as extremely vital infrastructure components, requiring greater awareness and better security and management. Securing Converged IP Networks provides contributed articles from the world's leading experts on convergence - leading Information and Communication Technology (ICT) practitioners - who offer expert advice on how to maintain content integrity and network assurance, advice that protects business uptime and prevents financial loss. Topics include enterprise risk management in the converged environment, threats and safeguards unique to the ICT world, assurance management, and future challenges.